ETHICS AS A FOUNDATION OF MANAGEMENT – A VALUABLE RESOURCE OR A RELIC IN THE TIMES OF CRISIS? - Joanna Hernik; Marcin Gębarowski (Jurnal Ilmiah Ekonomi Bisnis, 2012)
Following rules of activity, resulting from ethical norms accepted in given society, may be one of sources of a competitive advantage. Though, it can be presumed that not everybody is aware of the necessity as well as of advantages connected with activity running this way. In this aspect, the aim of the article to show Polish businessmen attitude towards challenges flowing from handling business in accord with ethics. All theoretical issues discussed herein pertain to the topic of business ethics. Empirical data presented in this paper were gathered by the authors during 410 interviews about ethics that were conducted with businessmen running small and middle firms. The main intention was to determine if obeying ethic rules is a real value for entrepreneurs. From obtained results the conclusion, that Polish businessmen declare the importance of ethics in their activity, but in practice the bulk of them does not remember any rules and does not recognize ethics as a footing of business, can be draw out.